2018
DOI: 10.1039/c8ra01879k
|View full text |Cite
|
Sign up to set email alerts
|

How the change of OMe substituent position affects the performance of spiro-OMeTAD in neutral and oxidized forms: theoretical approaches

Abstract: Effect of changing the position of OMe substituent on the electrochemical and optical properties of spiro-MeOTAD hole conductor in neutral and oxidized forms for use in perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Figure 3(a) shows the UV-vis spectrum of oxidized samples, along with which a spectrum for a pristine sample was also plotted for comparison. The appearance of the broad peak at around 500 nm indicated the indeed oxidization of HTL 31 . The peak in the range from 600 to 800 nm shifted with the increase of the process time, implies the higher oxidization degree of HTL with the treatment time 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(a) shows the UV-vis spectrum of oxidized samples, along with which a spectrum for a pristine sample was also plotted for comparison. The appearance of the broad peak at around 500 nm indicated the indeed oxidization of HTL 31 . The peak in the range from 600 to 800 nm shifted with the increase of the process time, implies the higher oxidization degree of HTL with the treatment time 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In the beginning, the synthetic methods of perovskite layers on the films comparison of PSCs under different conditions difficult. [25][26][27][28] New HTLs with 2D materials helped us to analyze the role of 2D perovskite materials accurately. We observed that direct contact of the 2D materials with either 3D perovskite layers or HTL was not necessary because significant improvements were observed by inserting insulating layers next to 2D materials and avoiding direct contact between them.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks for all samples at around 390 nm can be attributed to the absorption of spiro-OMeTAD. The broad peak around 500 nm shown in Figure b is believed as the indicator for the generation of oxidized spiro-OMeTAD (spiro-OMeTAD + ), so the pristine spiro-OMeTAD does not have this absorption peak. , However, the spiro-OMeTAD oxidized by KMnO 4 has higher absorption around 500 nm than the spiro-OMeTAD oxidized by O 2 , indicating that KMnO 4 can rapidly oxidize spiro-OMeTAD and provide a higher yield.…”
Section: Results and Discussionmentioning
confidence: 99%